RMDisease V2.0: an updated database of genetic variants that affect RNA modifications with disease and trait implication. Issue Volume 51:Issue D1(2023) (5th September 2022) - Song, Bowen; Wang, Xuan; Liang, Zhanmin; Ma, Jiongming; Huang, Daiyun; Wang, Yue; de Magalhães, João Pedro; Rigden, Daniel J; Meng, Jia; Liu, Gang; Chen, Kunqi; Wei, Zhen
Abstract: Recent advances in epitranscriptomics have unveiled functional associations between RNA modifications (RMs) and multiple human diseases, but distinguishing the functional or disease-related single nucleotide variants (SNVs) from the majority of 'silent' variants remains a major challenge. We previously developed the RMDisease database for unveiling the association between genetic variants and RMs concerning human disease pathogenesis. In this work, we present RMDisease v2.0, an updated database with expanded coverage. Using deep learning models and from 873 819 experimentally validated RM sites, we identified a total of 1 366 252 RM-associated variants that may affect (add or remove an RM site) 16 different types of RNA modifications (m 6 A, m 5 C, m 1 A, m 5 U, Ψ, m 6 Am, m 7 G, A-to-I, ac 4 C, Am, Cm, Um, Gm, hm 5 C, D and f 5 C) in 20 organisms (human, mouse, rat, zebrafish, maize, fruit fly, yeast, fission yeast, Arabidopsis, rice, chicken, goat, sheep, pig, cow, rhesus monkey, tomato, chimpanzee, green monkey and SARS-CoV-2). Among them, 14 749 disease- and 2441 trait-associated genetic variants may function via the perturbation of epitranscriptomic markers. RMDisease v2.0 should serve as a useful resource for studying the genetic drivers of phenotypes that lie within the epitranscriptome layer circuitry, and is freely accessible at: www.rnamd.org/rmdisease2 .